Serum protein profiles of juvenile ring-necked pheasants vaccinated or not against newcastle disease - Schmidt, Elizabeth Moreira dos Santos [UNESP]; Paulillo, Antonio Carlos [UNESP]; Rosangela, Locatelli-Dittrich; Beltrame, Olair; Denadai, Janine [UNESP] (My University, 2009)
The aim of this study was to investigate blood protein parameters in juvenile ring-necked pheasants using Ulster 2C, B1 and LaSota vaccines strains of the Newcastle disease virus. Total serum protein, albumin and globulin concentrations showed significantly differences among vaccinated and nonvaccinated birds. Significant variations were not observed in the analyses in relation to protein electrophoresis profile. © Asian Network for Scientific Information, 2009.
Keywords: Albumin; B1; Globulins; Newcastle disease; Phasianus colchicus; Serum proteins; Ulster 2C; Aves; Newcastle disease virus; Phasianidae